(untitled) (Research, Society and Development, 2020)
Covid-19 is not a local problem but a serious challenge to the public health, affecting different continents. It has been the subject of government actions from different spheres in the municipality of Garanhuns. This study aimed to analyze the infectivity rate of Covid-19, in Garanhuns, through the effective reproductive number of the new coronavirus. The effective reproductive number is often used in epidemiological models. For that, it was necessary to use an incidence graph and a parametric distribution that represented the probability of successive cases in the elapsed time. To ensure consistency of the estimate, use the ones for the mean and standard deviation of the distribution. We simulate the parameters according to a more recent literature on the subject, using more than one sample for projection in our analyzes. It emphasizes that we adapt the parameters according to the reality that an average infected patient takes to seek hospital care after the first symptoms of Covid-19. The results demonstrate, even a data analysis, as non-reduced measures, effectively, an infection and a value that allows indicating that the disease is no longer spreading. The study includes understanding the evolution of the pandemic and the effectiveness of public measures.